Occurrence of weed species in transplanted aman rice field as affected by cultivar - Mian, MAK; Matin, MA; Hossain, MA (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> In an ecological study of weed species in transplanted aman rice field, eight weed species were observed, namely Paspalum scrobiculatum L., Echinochloa colonum L., Fimbristylis littralis (L.) Vahl., Cyperus iria L., Alisma plantago L., Jussieua decurrens (Walt.) DC., Polygonum orientale L. and Sphenocelea zeylanica Gaertn. Among them Paspalum scrobiculatum L. was the most dominating species in respect of summed dominance ratio (SDR of 41.71) and relative dry weight (RDW of 60.18%). All weed species except A. plantago and J. decurrens were found dominant in semi-dwarf modern cultivars (BR11 and BR22) than in traditional tall cultivars (Nizersail and Biroi). The highest co-efficient of similarity was rendered by BR11 versus BR22 (91.22%), similarly by Nizersail versus Biroi (90.22%). All the cultivars demonstrated a positive relationship (r = 0.71 at p < 0.01) between weed growth and grain yield of rice. Â  Key words: Weed, Transplanted aman rice, Summed dominance ratio, Coefficient, Similarity, Cultivar doi:10.3329/bjb.v36i1.1554 Â  Bangladesh J. Bot. 36(1): 89-92, 2007 (June)